Perceptions and Acceptability of Artemisia annua Herbal Tea for Malaria Treatment: A Qualitative Study in Kalima Health Zone, Maniema, Democratic Republic of the Congo - Jerome Munyangi wa Nkola; Pierre Akilimali Zalagile; Hendrick Lukuke Mbutshu; Spartacus Kabala Munyemo; Imani Ramazani Bin Eradi; Alioune Camara (Healthcare, 2026)
Background: Malaria is a significant public health challenge in the Democratic Republic of the Congo. In conflict-affected areas, access to quality-assured ACTs is restricted by chronic stockouts and circulation of substandard and falsified antimalarials. This study investigates perceptions and social acceptability of Artemisia annua herbal tea in the Kalima Health Zone. Methods: Distinct from the prior provider-arm cross-sectional survey of the same program in the Kalima Health Zone which sampled only biomedical healthcare workers (n = 337), this exploratory qualitative study adopted a socio-anthropological design across three stakeholder strata (community users, biomedical providers, opinion leaders). Maximum-variation purposive sampling recruited 30 informants across five health areas (11 end-users, 11 providers, 8 opinion leaders). Sample-size adequacy was assessed against Malterud’s information power framework; data collection continued until operational thematic saturation. Hybrid inductive–deductive thematic content analysis followed COREQ reporting. Results: End-users demonstrated high willingness, driven by accessibility, perceived three-day recovery, and avoidance of unreliable ACTs. Biomedical providers voiced intense posological anxieties over uncalibrated raw biomass and sub-therapeutic dosing. Behavioral patterns were shaped by socio-religious norms and digitally mediated religious discourse. A unanimous demand for industrial galenic transformation of raw biomass into calibrated tablets emerged across all groups. Conclusions: This study does not validate the clinical efficacy, safety, posological adequacy, or resistance-attenuation potential of Artemisia annua herbal tea. It documents a transversal household-level consensus, across the three strata and five health areas, that Artemisia annua herbal tea adoption responds to documented double ACT supply chain failure. A unanimous demand for industrial galenic transformation emerged across all stakeholder groups.